The Influence of The "Exicor" Approach On Learning Interest Of 4th Grade Students In Science Lessons - Naintyn Novitasari (JSEP (Journal of Science Education and Practice), 2020)
This study aims to determine the increase in students' interest in learning using the EXICOR approach and the effect of the EXICOR approach on the Learning Interest of Class IV Students in Science Subjects at MIN 02 Bengkulu City. The type of research used is descriptive quantitative. The sample in this study amounted to 30 students of class IV MIN 02 Bengkulu City consisting of experimental class IVb and control class IVa. The data collection techniques in this study used questionnaires and documentation techniques. The data analysis technique used the T-test with the help of the Statistical Product For Servicer Solution (SPSS) Program 25. From the application of the EXICOR approach it was used to increase student interest in learning while the average value for student interest in class IVb was 78.53 and in class IVa 63, 13. Based on the results of the research from the variable X and Y variable questionnaires. . Then t arithmetic 4,383 t table 2,048 so it can be concluded that Ho is rejected and Ha is accepted. And from the calculation of the coefficient of determination (R Square) of 0.596, this value means that the effect of the EXICOR Approach (X) on students' learning interest in science subjects (Y) is 59.6% while 40.4% is influenced by other factors. which were not researched.